Intraoperative Imaging in Ovarian Cancer: Fact or Fiction? - Lucia M.A. Crane; Marleen van Oosten; Rick G. Pleijhuis; Arash Motekallemi; Sean C. Dowdy; William A. Cliby; Ate G.J. van der Zee; Gooitzen M. van Dam (Molecular Imaging)
Tumor-targeted fluorescence imaging for cancer diagnosis and treatment is an evolving field of research that is on the verge of clinical implementation. As each tumor has its unique biologic profile, selection of the most promising targets is essential. In this review, we focus on target finding in ovarian cancer, a disease in which fluorescence imaging may be of value in both adequate staging and in improving cytoreductive efforts, and as such may have a beneficial effect on prognosis. Thus far, tumor-targeted imaging for ovarian cancer has been applied only in animal models. For clinical implementation, the five most prominent targets were identified: folate receptor α, vascular endothelial growth factor, epidermal growth factor receptor, chemokine receptor 4, and matrix metalloproteinase. These targets were selected based on expression rates in ovarian cancer, availability of an antibody or substrate aimed at the target approved by the Food and Drug Administration, and the likelihood of translation to human use. The purpose of this review is to present requirements for intraoperative imaging and to discuss possible tumor-specific targets for ovarian cancer, prioritizing for targets with substrates ready for introduction into the clinic.